Mengungkap Karakter Kreatifitas 3 Karya Nirmana Dwi Matra - Yuliansyah, Hendy (Pascasarjana ISBI Bandung, 2020)
Nirmana dwi matra as one and the basis for the introduction of works of art into works is still rare but is in demand by the public. It is an interesting visualization but it is difficult to understand the meaning or meaning in the work of nirmana dwi matra. The various types of nirmana dwi matra works with visualization going hand in hand with certain goals have led to an increase in people’s insight into the work of nirmana dwi matra. Through this research, using descriptive analysis method, through art theory and classification, nirmana dwi matra has the potential to become an expert in the form of material, aesthetics, imagination, color harmonization, crossing the concept of performance, recording media, and visualization.Keywords: expert, aesthetics, imagination, nirmana, art, color.